HAPPINESS ORIENTATIONS AMONG ADOLESCENTS RAISED IN URBAN AND RURAL AREAS - Anisti Anggraeny; Kwartarini Wahyu Yuniarti; Moordiningsih moordiningsih; Uichol Kim (Indigenous, 2015)
Researcher takes particular interest to discover the respondents’ orientation towards happiness based on where the respondent was raised. The study involves 467 senior high school students with ages ranging from 14-17 years old. The data is analyzed using an adapted society psychological approach. The results shows that adolescents raised in rural areas are consider the family to be a factor that contributes to their happiness. Second, achievement is also a factor that leads to happiness. However for the category, to love and be loved, adolescents growing in urban areas place this as a factor that leads to happiness. Similar with spirituality, friends and leisure time are factors that make adolescents raised in urban areas to become happy. Nevertheless, the results of cross tabulation with Pearson chi square test scoring demonstrates that no correlations exist between adolescent happiness raised from urban or rural areas.